KORELASI ANTARA KECEMASAN MATEMATIS DAN HASIL BELAJAR MATEMATIKA SISWA: STUDI META-ANALISIS DI INDONESIA - Suci Tawaldi, - (2022)
Suci Tawaldi (2022). The Correlation Between Mathematics Anxiety and Students' Mathematics Learning Outcomes: Meta-Analysis Study in Indonesia Previous researches have conducted various meta-analysis studies about mathematics anxiety and students' mathematics learning outcomes. However, none of these studies have focused yet on the Indonesia region. This study aims to synthesize and to examine the correlation strength between mathematics anxiety and the students' mathematics learning outcomes. It synthesizes and investigates several moderator factors that can potentially cause heterogeneity. Some of those are education level and students' demographics. In this research, 31 empirical studies collected between 2010 and 2021 have identified and synthesized statistically uses the meta-analysis technique. The research shows that a low negative and statistically significant correlation exists (r = - 0,197) between mathematics anxiety and the mathematics learning outcomes for students. Furthermore, the moderator analysis result shows that the heterogeneity correlation does not emerge significantly due to the education level factor and the students' demography. This study provides information and insights to educators, practitioners, and parents to understand that it is important to pay attention to students who experience anxiety and how to overcome and reduce the anxiety level to achieve successful mathematics learning outcomes. Keywords: Mathematics Anxiety, Students' Mathematics Learning Outcomes, Meta-Analysis.